Kepemimpinan Inklusif Dalam Proses Pembangunan Komunitas Dengan Mendorong Partisipasi Dan Pemberdayaan Anak Muda - Miranda Agnelya Naibaho; Hairani Siregar (BADAN PENERBIT STIEPARI PRESS, 2023)
In community development, inclusive leadership is crucial for empowering and involving young people. This research uses a participatory approach to understand how inclusive leadership positively affects communities and the unique contributions of young individuals. The findings shape an implementation program, including leader training and strategies for enhancing youth participation. Continuous evaluation ensures the program's success and adaptability. The discussion highlights the need for collaboration, community education, and ongoing evaluation. In conclusion, inclusive leadership is essential for creating a fair, sustainable, and innovative society, prioritizing positive changes and strengthening the role of young people in sustainable development.